Foot length as a screening tool for identification of preterm babies: a cross sectional study - Tenali, Ananya S. L.; Tenali, Ravi Kumar (International Journal Of Community Medicine And Public Health, 2019)
Background: India is one of the countries with the highest neonatal mortality, for which preterm birth is considered as major cause (43.7%). Therefore, early identification by a simple screening tool is important for prognostication and follow-up of new-born infants, especially preterm. Methods: Cross-sectional study was conducted on 300 live newborns at Saveetha Hospital in Kanchipuram. Anthropometric measures such as birth weight, crown-heel length, head circumference, foot length were taken within 3 days of life and gestational age assessment was done by new Ballard scoring after calculation by Naegles formula. Neonates were grouped into preterm, term and post-term and also small for gestational age (SGA), appropriate for gestational age (AGA) and large for gestational age (LGA). Minimum to maximum range of variables in each gestational range was calculated. The sensitivity and specificity of each variable was found using receiver operating curve. Parameter having the highest sensitivity and good specificity was considered as potential screening tool to identify high risk babies. SPSS Software version 17 for windows was used. Results: The range of gestational age, length, foot length, birth weight and head circumference was 28-42 weeks, 35-53 cm, 5-8.8 cm, 0.8-4.7 kg and 22.8-54.3 cm respectively. Among all, maximum sensitivity at 37weeks gestational age was seen with foot length (80.57%) at a cut-off of 7.58 cm. A nomogram of foot length for each gestational age group (range of 2 weeks) was also derived. Conclusions: It can be concluded that foot length has the potential to be considered as a screening tool to identify preterm neonates especially at a concentrated community level and is particularly useful in resource constraint countries.